(untitled) (Acta Entomologica Serbica, 2022)
Habrobracon hebetor Say is an important biological control agent that has a wide range of lepidopteran hosts, especially from the Noctuidae and Pyralidae families. Nutrition is a very important element in the efficiency of natural enemies in integrated pest management (IPM). In the presented research, the sublethal effects of five selected chemical and botanical insecticides, fenvalerate, propargite, buprofezin, dayabon and palizin, on the activity of amylase and protease enzymes in the midgut of this important ectoparasitoid wasp were studied under laboratory conditions. Changes in the activity of enzymes were investigated by LC30 treatment of the female wasps, which were 0.14, 7.01, 3.04, 9.58 and 2.53 mg a.i./mL, respectively. The obtained results showed that this parasitoid wasp has a long midgut in its digestive tract. Also, there were significant differences among the enzymatic treatments (F5,12 =14.695 and 99.278) except protein concentration (F5,12 = 0.670). Regarding the amylase enzyme, the highest and lowest activities were obtained in the control and fenvalerate treatment (0.0435±0.0023 mU/mg vs. 0.0277±0.0010 mU/mg). In addition, the highest proteolytic activity was observed in the control (4.9817±0.0268 U/mg) and the lowest in the propargite treatment (3.2231±0.0917 U/mg). By closely investigating the results, dayabon and palizin showed the lowest negative effects on the enzymes and could be applied together with this parasitoid wasp in IPM designs.